Insight into the Exoproteome of the tissue derived trypomastigote form of Trypanosoma cruzi - Queiroz, Rayner Myr Lauterjung (2016)
The protozoan parasite Trypanosoma cruzi causes Chagas disease, one of the major neglected infectious diseases. It has the potential to infect any nucleated mammalian cel . The secreted/excreted protein repertoire released by T. cruzi try pomastigotes is crucial in host-pathogen interactions. In this study, mammalian tissue culture derived trypomastigotes (Ystrain) were used to characterize ethe exoproteome of the infective bloodstream life form. Proteins released into the serum free culture medium after 3h of incubation were harvested and digested with trypsin. NanoLC MS/MS analysis resulted in the identification of 540 proteins, the largest set o freleased proteins identified to date in Trypanosoma spp. Bioinformatic analysis predicted most identified proteins as secreted, predominantly by non- classical pathways, and involved in host-cell infection.Some proteins possess predicted GPI-anchor signals, these being mostly trans-sialidases, mucin associated surface proteins and surface glycoproteins. Moreover, we enriched phosphopeptides and glycopeptides from tryptic digests. The majority of identified glycoproteins are trans-sialidases and surface glycoproteins involved in host-parasite interaction. Conversely, most identified phosphoproteins have no Gene Ontology classification. The existence of various proteins related to similar functions in the exoproteome likely reflects this parasite’s enhanced mechanisms for adhesion, invasion, and internalization of different host-cell types, and escape from immune defenses.